2013
DOI: 10.15232/s1080-7446(15)30224-2
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Updated scientific evidence on the welfare of gestating sows kept in different housing systems

Abstract: Gestation sow housing is a contemporary animal welfare issue with legislative actions in the United States to ban individual gestation sow systems. This review sought to summarize the scientific literature since earlier reviews were published in 2004 and 2005. Seventeen papers comparing effect of housing systems on the welfare of gestating sows were published from 2005 to 2012. Stalls or crates, tether housing, and group pens including conventional group pens, loose-house pens, electronic sow feeders pens, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Aiming to characterize behavioral aspects of pregnant sows, the average frequencies of the sitting position were observed for female swine housed in individual cages and in collective stalls, resulting in 4.40% and 0.58% for each type of housing (PANDORFI, 2005).Staying seated or standing inactive for long periods may indicate poor welfare. The lying position, on the other hand, may reflect a good welfare situation in the case of sows housed in collective stalls (McGLONE, 2013). The behaviors of inactive activity (Figure 2), alert and sniffing showed statistical differences (P <0.05) in both stages.…”
Section: Resultsmentioning
confidence: 94%
“…Aiming to characterize behavioral aspects of pregnant sows, the average frequencies of the sitting position were observed for female swine housed in individual cages and in collective stalls, resulting in 4.40% and 0.58% for each type of housing (PANDORFI, 2005).Staying seated or standing inactive for long periods may indicate poor welfare. The lying position, on the other hand, may reflect a good welfare situation in the case of sows housed in collective stalls (McGLONE, 2013). The behaviors of inactive activity (Figure 2), alert and sniffing showed statistical differences (P <0.05) in both stages.…”
Section: Resultsmentioning
confidence: 94%
“…Stall housing is commonly used in the United States during the gestation phase (McGlone, ), which can be divided into early and mid‐to‐late stages. Since 2013, group housing in European Union countries was deemed mandatory from 4 weeks after breeding to 1 week before the due date (European Commission, ), and floor space allowances in pen housing for pregnant gilts only and for sows combined with gilts, in groups of 6–40 pigs, are required to be 1.64 and 2.25 m 2 per pig, respectively (Maes, Pluym, & Peltoniemi, ).…”
Section: Four Production Phases In Gilts and Sowsmentioning
confidence: 99%
“…McGlone and colleagues reviewed the literature from 1970 to 2002, and concluded that no differences were discernable between individual stall housing and group housing for PBA (9.8 vs. 9.9 pigs, respectively) or farrowing rate (80.6% vs. 75.9%, respectively)(McGlone et al, ). A more recent review by McGlone looked at the results of studies from 2005 to 2012 (McGlone, ), again reporting no differences in PBA between individual stall housing and group housing from six primary studies (Chapinal et al, ; Harris et al, ; Hulbert & McGlone, ; Jansen, Kirkwood, Zanella, & Tempelman, ; Karlen et al, ; Salak‐Johnson, Niekamp, Rodriguez‐Zas, Ellis, & Curtis, ). Assessment of pens retrofitted from stalls identified no differences in PBA between various pens and stalls, so long as the area was 1.5 m 2 per sow (Johnston & Li, ).…”
Section: Four Production Phases In Gilts and Sowsmentioning
confidence: 99%
“…Considering animal welfare science, we have a very interesting situation. The totality of the science, as reviewed by four groups over time [ 13 , 20 , 21 , 22 ] suggests that the welfare, on average, does not differ however, one EU review [ 23 ] concluded the welfare of sows in gestation crates was lower than when they are in group housing.…”
Section: Example #2: Gestation Sow Housing Systems: Crates mentioning
confidence: 99%